2016
DOI: 10.1097/bot.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac Administered in the Recovery Room for Acute Pain Management Does Not Affect Healing Rates of Femoral and Tibial Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Likewise, Giannoudis et al 30 suggested a significant association of poor bone healing outcomes with ibuprofen/diclofenac exposure, for a mean duration of 21.2 weeks, during the postoperative period (p < 0.00001). In contrast, Donohue et al 64 reported no increased risk of complications with the use of standard-dose IV/IM ketorolac for 24 h in the immediate post-operative period. Although the results were not statistically significant (p ¼ 0.25), the reported narrow confidence interval (OR ¼ 0.58, 95% CI 0.23-1.46) highlights them as accurate and relevant within clinical settings (Table 4).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Likewise, Giannoudis et al 30 suggested a significant association of poor bone healing outcomes with ibuprofen/diclofenac exposure, for a mean duration of 21.2 weeks, during the postoperative period (p < 0.00001). In contrast, Donohue et al 64 reported no increased risk of complications with the use of standard-dose IV/IM ketorolac for 24 h in the immediate post-operative period. Although the results were not statistically significant (p ¼ 0.25), the reported narrow confidence interval (OR ¼ 0.58, 95% CI 0.23-1.46) highlights them as accurate and relevant within clinical settings (Table 4).…”
Section: Resultsmentioning
confidence: 93%
“…Reuben and Ekman 56 Randomised trial Fraudulent allegations reported in literature 69 11 retrospective cohort studies, 37,39,41,42,44,45,[62][63][64][65][66] two case-control studies 30,67 and two prospective randomised trials 40,46 ( Tables 2 and 3) that underwent qualitative analysis, of which eight retrospective cohort studies 37,39,41,42,44,45,62,64 and two case-control studies 30,67 on adult populations formed part of the meta-analysis. Table 4 shows the abstraction data and statistical parameters for all analysed studies.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term use of NSAIDs and the severity of concomitant injuries may both have a negative effect on bone healing due to interference in the acute inflammation stage of fracture healing. [7] We used the administration of analgesics for more than 3 consecutive months and admission of more than 2 weeks as risk factors representing concomitant or more severe injuries. The results revealed no significance over the three risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The radiographic part was defined as when no visible progressive signs of healing were identified for at least 3 consecutive months, when the fractured bone had not healed within 9 months, or if the orthopaedic surgeon considered the fracture to have little or no chance of healing. [7] The clinical part was defined as persistent pain and soreness feeling of the thigh during walk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation